Impact resistance of a rectangular polycarbonate armor plate subjected to single and multiple impacts - Hussain Shah, Qasim (Elsevier, 2009)
In the present work the plastic deformation of a thin rectangular polycarbonate armor plate subjected to single and multiple impacts was investigated in detail. The impacts were conducted on a horizontal and diagonal path to explore the plate vulnerability against the in-coming single and multiple projectiles striking at various locations. Single impacts revealed the overall trend in plate dent sizes and thickness reductions on the horizontal and diagonal paths. Results were compared with previous research [Shah QH, Abakr YA. Effect of distance from the support on the penetration mechanism of clamped circular polycarbonate armor plates. International Journal of Impact Engineering 2008;35:1244–50] conducted on circular armor plate for validation purposes. The single impact data scatter necessitated to conduct repeated impact tests at reduced number of locations to search for a definite answer for the possible failure process in the vicinity of the clamped edges of the plate. An accelerated plastic deformation resulting in early perforation was found to occur in the diagonal plate corner compared to the plate center impact position or close to a straight clamped edge. Multiple impact results presented can be significantly helpful in designing rectangular shape polycarbonate armor plates to enhance safety. LSDYNA was used to simulate the impact event for the plate midpoint, the horizontal edge, and the diagonal edge. The results show a close agreement with the experimental work.